Relationships of Empathy and Color-blind Attitudes on Counseling Students’ Critical Consciousness - Bagmi Das; Maggie M Parker; Sarah Litt (Teaching and Supervision in Counseling, 2024)
A critical piece of counselor education is enhancing counselors’ in training (CITs) multicultural competence. Concepts included in CIT cultural development include both developing empathy (Constantine, 2001) and dismantling color-blind racial attitudes` (Neville et al., 2013). Thus, this study presents multiple regression to explore the relationships between color blindness, empathy development, and critical consciousness of 166 counseling students. Results indicate that that empathy and color-blind attitudes have associations with some aspects of critical consciousness, but not sociopolitical participation. Implications for counselor education and directions for future research are discussed.
Keywords: empathy; colorblindness; critical consciousness; counselor training; regression